2021
DOI: 10.1097/cin.0000000000000760
|View full text |Cite
|
Sign up to set email alerts
|

Building a Handoff Communication Virtual Experience for Nursing Students Using Virtual Humans

Abstract: Effective communication among healthcare professionals is critical to delivering safe, high-quality patient care. One important real-world skill that nursing students must acquire is generating accurate handoff communication reports. The central aim of this study was to build, assess, and revise a virtual experience simulation that allows nursing students to observe a standardized clinical situation in an immersive environment and then practice the situation-background-assessment-recommendation communication m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Nurse educators, dealing with increasingly more tired and unmotivated students in this period, clearly saw the need to develop new strategies. 8,9,27,28 The results of our study using animation and gamification methods with the generation Z nursing students who were in fact born into technology showed that the use of animation and gamification in online distance learning in nursing students increased their knowledge as well as motivation. [29][30][31] There have been reports of positive cognitive outcomes achieved in learners with the inclusion of technology in teaching methods.…”
Section: Discussionmentioning
confidence: 84%
“…Nurse educators, dealing with increasingly more tired and unmotivated students in this period, clearly saw the need to develop new strategies. 8,9,27,28 The results of our study using animation and gamification methods with the generation Z nursing students who were in fact born into technology showed that the use of animation and gamification in online distance learning in nursing students increased their knowledge as well as motivation. [29][30][31] There have been reports of positive cognitive outcomes achieved in learners with the inclusion of technology in teaching methods.…”
Section: Discussionmentioning
confidence: 84%
“…Virtual reality nursing related systems transfer health care knowledge, which can be applied in schools, practice bases, and clinical practice. Virtual humans can be built in a virtual world to show anatomical knowledge or develop nurse-patient communication skills ( 20 , 21 ). Various types of operational training, such as catheterization or tracheal insertion ( 22 , 23 ), can be realized using the same virtual scene as in an actual laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative needs assessment of NICU training, Koo and Lee [4] reported that students needed substantial handoff observation and practice. Therefore, providing systematic handoff training through undergraduate nursing education to enhance the ability of nursing students to accurately communicate among medical staff is necessary [29].…”
Section: Introductionmentioning
confidence: 99%